2016
DOI: 10.1007/s00425-016-2539-x
|View full text |Cite
|
Sign up to set email alerts
|

Glandular trichomes of Tussilago Farfara (Senecioneae, Asteraceae)

Abstract: The glandular trichomes are developed on the aerial organs of Tussilago farfara ; they produce phenols and terpenoids. Smooth endoplasmic reticulum and leucoplasts are the main organelles of the trichome secretory cells. The aim of this study was to characterise the morphology, anatomy, histochemistry and ultrastructure of the trichomes in Tussilago farfara as well as to identify composition of the secretory products. Structure of trichomes located on the peduncles, bracts, phyllaries, and leaves were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Moreover, in the trichomes of these three species, TEM observations revealed that the cuticle became distended and separated from the cell walls of the head cells and formed a subcuticular space. A leucoplast that contained lamellae with osmiophilic inclusions was described from the secretory cell of the trichomes that produce phenols and terpenoids in Tussilago farfara and other Asteraceae species (Muravnik et al 2016, and literature therein). Muravnik et al (2016) suggested that the black deposition in the lamellae correspond to terpene precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the trichomes of these three species, TEM observations revealed that the cuticle became distended and separated from the cell walls of the head cells and formed a subcuticular space. A leucoplast that contained lamellae with osmiophilic inclusions was described from the secretory cell of the trichomes that produce phenols and terpenoids in Tussilago farfara and other Asteraceae species (Muravnik et al 2016, and literature therein). Muravnik et al (2016) suggested that the black deposition in the lamellae correspond to terpene precursors.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that microbodies actively participate in the production of secondary metabolites such as terpenoids and phenolic substances (e.g. Vassilyev 2000; Muravnik et al 2016). The lipid bodies in the cytoplasm and/or plastids with lipid globules were frequently recorded in osmophore tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of special storage structures in the root possibly containing terpenoids was investigated by a histochemical analysis using NADI (dimethyl-pphenyl-enediamine and a-naphthol) staining (David and Carde, 1964;Caissard et al, 2004;Jezler et al, 2013;Kromer et al, 2016;Muravnik et al, 2016;Steševi c et al, 2016;Stoji ci c et al, 2016). The NADI reagent has been reported to give rise to a blue/purple color in the presence of oxygenated or lipophilic compounds (e.g.…”
Section: Histochemical Analysis Of T Garganica Rootsmentioning
confidence: 99%
“…Apart from chemical drying, some researchers tend to use air drying method, which often resulted in producing tissue distortions (Zimmer 1989). In plants, glandular trichomes are considered as one of the most delicate surface structures (Muravnik et al 2016). In this study, we report our findings of SEM analysis on leaf glandular trichomes of Millingtonia hortensis, a tree species of Bignoniaceae widely distributed throughout south-east Asia, with an aim to reassess the CPD, HMDS and air-drying methods.…”
Section: Introductionmentioning
confidence: 97%